Ascertained performance deduction based on key performance indicators guided by JKR Wilayah Persekutuan Putrajaya / Siti Rohayu Ismail - Ismail, Siti Rohayu (Universiti Teknologi Mara, Perak, 2014)
Ascertained performance deduction (APD) is the procedure to deduct the monthly payment based on key performance indicators (KPI) guided by JKR Wilayah Persekutuan Putrajaya. The verifier is the person in charge to deduction payment in ascertained performance deduction (APD). The deduction is making or calculates from their maintenance contractor performance and availability. Other than that, computerized maintenance management system (CMMS) is one of the important sources to calculate the deduction of payment for the every monthly. For example every corrective maintenance, preventive maintenance, breakdown, open work order and close work orders have information in CMMS. Besides, customer satisfaction is also important in key performance indicator (KPI) and to avoid the deduction in ascertained performance deduction (APD). It is because, if the customer or client unsatisfied maybe the performance and service that give of service provider (contractor) is bad and low quality. Every item at key performance indicators (KPI) must be follow by service provider (contractor) to avoid higher deduction in ascertained performance deduction (APD). Last but not least, the good performance and service from service provider (contractor) to get an excellent result for ascertained performance deduction (APD). As a conclusion, key performance indicators (KPI) are very important to measure the level of the performance of service provider (contractor) during their contract at the building. So that, the contractor must has a smart plan to arrange the organizational maintenance management in the building to be systematic and goes according to plan as long as will be a good contractor in maintenance industry.